KEMAMPUAN MEMBACA AWAL MELALUI MEDIA SANDPAPER LETTERS PADA ANAK KELOMPOK A (STUDI KASUS DI RA SYIHABUDDIN MALANG) - Alya Nur Fadhilah; Ika Ratih Sulistiani; Eko Setiawan (UNISMA, 2021)
Stimulating the ability of children’s early reading is important. Reading means to transfer the knowledge, to transfer the information and for a communication. RA Syihabuddin Malang stimulates early reading to the childrens of the group A with sandpaper letters media. Sandpaper letters is an effective media to stimulate children’s early reading. Sandpaper letters media involved the stimulus of language development aspect, cognitive development aspect and motoric development aspect. This research is a qualitative with study case approached, the subjects are 17 childrens of the group A with around 4-5 years old. The data was collected by an interview and an observation of the subjects. The result of this research is childrens ability of early reading of the group A are has developed. Any of the childrens can read words, some of them are have an ability to get to know the alphabets, and two of them needs to get more stimulus. What teacher needs to stimulate more are (p, q, b, d, m, n, u, v, w) because they are seems similar.